2018
DOI: 10.1007/s00704-018-2372-1
|View full text |Cite|
|
Sign up to set email alerts
|

Observed changes in extreme precipitation in Poland: 1991–2015 versus 1961–1990

Abstract: Several episodes of extreme precipitation excess and extreme precipitation deficit, with considerable economic and social impacts, have occurred in Europe and in Poland in the last decades. However, the changes of related indices exhibit complex variability. This paper analyses changes in indices related to observed abundance and deficit of precipitated water in Poland. Among studied indices are maximum seasonal 24-h precipitation for the winter half-year (Oct.-March) and the summer half-year (Apr.-Sept.), max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 34 publications
(46 reference statements)
1
40
0
Order By: Relevance
“…Change detection in observation records of climatic variables in Poland was carried out for a range of variables of particular relevance and interest, such as temperature (Graczyk et al 2017), mean precipitation (Pińskwar et al 2018b;Szwed 2018), as well as intense precipitation (Pińskwar et al 2018a) and snow cover (Szwed et al 2017).…”
Section: Change Detection In Observed Climate Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Change detection in observation records of climatic variables in Poland was carried out for a range of variables of particular relevance and interest, such as temperature (Graczyk et al 2017), mean precipitation (Pińskwar et al 2018b;Szwed 2018), as well as intense precipitation (Pińskwar et al 2018a) and snow cover (Szwed et al 2017).…”
Section: Change Detection In Observed Climate Datamentioning
confidence: 99%
“…The most visible increases in the monthly precipitation totals as well as in the share of monthly precipitation within the annual total were found during the colder half-year, especially in March, with statistically significant trend detected for several stations in the northern and central parts of Poland. Pińskwar et al (2018a) noted the occurrence of many episodes of extreme precipitation excess and deficit in Europe and in Poland in recent decades that had caused considerable, and adverse, economic and social impacts. In Poland, the changes in values of climate indices were found to exhibit complex, spatial and temporal, variability.…”
Section: Change Detection In Observed Climate Datamentioning
confidence: 99%
“…Yet, there are regionally consistent seasonal changes and precipitation increase in spring and winter dominates. Pińskwar et al (2018b) showed that daily maximum precipitation for the summer half-year (Apr.-Sept.) increased for many stations and there were more positive changes during the summer halfyear than those in the winter half-year (Oct.-March). Szwed et al (2017) found that observed tendencies in time series of snow-related variables is complex and not easy to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…in precipitation-based drought indices by Somorowska (2016). Pińskwar et al (2018a) analysed changes in observed daily precipitation records in Poland from 1951 to 2015. Trends were detected, but mostly weak and statistically insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation plays a critical role in the global hydrological cycle and energy exchange of the atmosphere [1][2][3][4]. The uneven distribution of precipitation over large areas may directly cause the hydrologic system to be unstable [5][6][7] and easily lead to urban flooding, mountain mudslides, and flash floods [8][9][10].…”
Section: Introductionmentioning
confidence: 99%